Maximizing the Impact of Training Initiatives for Health Professionals in Low-Income Countries: Frameworks, Challenges, and Best Practices - Cancedda, Corrado; Farmer, Paul E.; Kerry, Vanessa; Nuthulaganti, Tej; Scott, Kirstin W.; Goosby, Eric; Binagwaho, Agnes (PLOS Medicine, 2015)
Corrado Cancedda and colleagues outline a framework for health professional training initiatives in low-income countries.